The Role of The operations Component in Customers' Appetite for Dealing with private Banks A Field Study on Clients of private Banks in Lattakia Governorate - naser, somar; Dima Makhous, (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aimed to clarify the role of the operations component in its four dimensions (the degree of complexity of the procedures for obtaining banking service, the customer's participation in operations, the degree of standardization of banking service, the place of providing banking service) in the customers' appetite for dealing with private banks. The researchers followed the descriptive approach in his study, and a group of methods, including relying on primary data through a questionnaire that was designed by informing the researcher of the published literature, and it was distributed to an easy sample consisting of (300) respondents, of which (295) were retrieved, and it was (290) a questionnaire Valid for analysis, and the research community consisted of clients of private banks, and then the 23SPSS program was relied on to analyze the available data. The study concluded that there is a positive role for the dimensions of the operations element represented by (the degree of complexity of procedures for obtaining banking service, the customer’s participation in operations, the degree of standardization of banking service, the place of providing banking service) in the demand of customers to deal with private banks, where the correlation coefficient reached (0.853). ) which indicates an acceptable and direct correlation between the dimensions of the operations component and customer demand .